2020
DOI: 10.1002/cae.22318
|View full text |Cite
|
Sign up to set email alerts
|

Education in times of crisis: Rapid transition to distance learning

Abstract: The COVID‐19 crisis is having a significant impact on the quality of life and future of young people; it can also lead to disruption in education. A disruption would pose a severe threat to the entire society in the postcrisis period. Therefore, educational institutions must respond quickly and ensure the continuity of the educational processes. Our research goal has been to develop and implement a model enabling a rapid transition from the traditional to the distance learning model in a state of emergency. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
101
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 32 publications
3
101
0
8
Order By: Relevance
“…Bao (2020) was perhaps the first to describe how universities were moving from classroom‐based education to online education because of the raging pandemic. Researchers have tried to understand the viewpoint of students on online education during the COVID‐19 pandemic using empirical studies in India (Mishra, Gupta, & Shree, 2020), Serbia (Bojovic, Bojovic, Vujosevic, & Suh, 2020), and USA (Patricia, 2020).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Bao (2020) was perhaps the first to describe how universities were moving from classroom‐based education to online education because of the raging pandemic. Researchers have tried to understand the viewpoint of students on online education during the COVID‐19 pandemic using empirical studies in India (Mishra, Gupta, & Shree, 2020), Serbia (Bojovic, Bojovic, Vujosevic, & Suh, 2020), and USA (Patricia, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…However, no university was ready for a complete shift to online education. Empirical studies have found that students feel that they learn better in physical classrooms than through online education (Bojovic et al, 2020). Students miss the help they receive from their peers in classrooms and laboratories and access to library (Patricia, 2020).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…La aparición del COVID 19 en China -y que se propagase en todo el mundo durante el 2020llevó a una modificación sin precedentes sobre la forma de vivir y, en específico de aprender, mismas que se tuvieron que adaptar a un confinamiento impuesto por cada gobierno nacional (Bojović et al, 2020;José et al, 2020;Luna-Nemecio & Tobón, 2021;Nassr et al, 2020;Villegas-Ch et al, 2020;Wang et al, 2020). En situaciones inesperadas como ésta, la educación basada en herramientas virtuales puede ser de gran ayuda (Romero-Rodriguez et al, 2020).…”
Section: Introductionunclassified
“…Las investigaciones actuales muestran y analizan la forma en que el software educativo apoya en los programas de enseñanza en todos los niveles (Campos et al, 2020;Estany et al, 2017); tanto de forma parcial, con el uso de un software para realizar algunas prácticas o experimentos virtuales, como de forma global, con la utilización de un software como acompañamiento de todo el desarrollo de un curso educativo, señalan, las ventajas y desventajas que dicho software supone, las habilidades necesarias para su empleo y la forma de utilización (Bojović et al, 2020;Kalu, 2018;Karvinen & Karvinen, 2018;Kholis et al, 2018;Melo-Solarte et al, 2018;Rodríguez-Alabanda et al, 2019). Es inaplazable el análisis de la adecuación de los softwares, más utilizados en el TecNM, hacia una aplicación específica y adaptada a un programa educativo de una asignatura.…”
Section: Introductionunclassified